IDENTIFIKASI PENYEBAB TINGGINYA JUMLAH KASUS TUBERCULOSIS PARU DI PROVINSI RIAU - Dewi Asri, Irma; Mitra, Mitra; Anusirwan, Anusirwan (Ensiklopedia of Journal, 2024)
Pulmonary TB is still a health problem that must be faced in Indonesia, especially in Riau Province. In 2022, Indonesia will be in second place with the highest number of pulmonary TB sufferers in the world after India. Meanwhile, in 2021, Riau Province will be in tenth position with the highest number of TB in Indonesia. The aim of this research is to identify the problems and causes of the high number of pulmonary TB cases from 2018 to 2022 in Riau Province. The research method begins quantitatively with a descriptive design and continues with qualitative research using a case study approach. Data collection techniques were carried out using interviews, observation and documentation. The data sources used include primary data and secondary data. In quantitative data analysis, it was found that the number of pulmonary TB cases increased, the pulmonary TB death rate increased, the Treatment Coverage achievement of cure rates and BCG immunization did not reach the target and the number of pediatric pulmonary TB cases increased. The causes of the still high number of pulmonary TB cases in Riau Province were identified through qualitative analysis using the problem tree method. Several factors are causing the pulmonary TB problem in Riau Province, namely Treatment Coverage has not reached the national target, there is transmission in the community, the cure rate for pulmonary TB has not reached the national target and an increase in the number of pediatric pulmonary TB cases. It is recommended that the Riau Provincial Health Service carry out monitoring and evaluation of the achievements and challenges of controlling pulmonary TB in Riau Province.Keywords: Identification, Causes, Pulmonary Tuberculosis, Riau Province